'Don't Ask, Don't Tell': Silence in Northern Ireland Christian Churches Regarding Issues of Sexuality. Issue 3 (3rd July 2017) - Fegan, Conor J.
Abstract : Lesbian, gay, bisexual, transgendered and queer (LGBTQ) Christians face a culture of 'Don't ask, Don't tell, ' in regards to their sexuality from the three largest Christian denominations in Northern Ireland. This article explores the experiences of LGBTQ Christians in Northern Ireland; their views on this culture and the impact silence from many within their churches have, on both their faith and their wider lives. There are many within the Christian churches in Northern Ireland who are quietly supportive of queer members, however, there is a paucity of open and honest dialogue. I propose a renewed approach to hospitality within churches, with an understanding of all Christians as equally 'Beloved of God.' Leading to a situation where queer and non-queer alike, would have the space to understand and discus the problematic situation that currently exists and remove the barriers that prevent equality for LGBTQ members within faith communities.